O lazer na política pública de esporte: uma análise do Programa Segundo Tempo - Sheylazarth Presciliana Ribeiro (2012)
In the past few years discussions related to the public policy of sports and leisure have been the main focus of many studies, especially since the Constitution of 1988 considered sports and leisure to be a social right which leads to the need of implementation of programs in such areas. However, there are many limits on the development of actions in the public policy of sports and leisure and the development of knowledge has been contributing to the possibility of intervention by the State. A aspect that deserves focus is the understanding of leisure present in programs and actions developed by the public sector and this way, the goal of this research is to analyze how leisure is dealt with in the formation of professionals of the Programa Segundo Tempo from the Secretaria de Esporte Educacional of the Ministério de Esportes da União. Although the program focuses on educational sport, the connections with leisure can be established if we take as reference the questions of the time in which the actions are developed, the activities completed, and even the attitude of the individual when facing the possibilities, and even the actual space. As methodology I used a bibliography review, document research and analysis of PST documents as well as research using semi-structured interviews with 2 managers of the PST capacitation process, all data was analyzed. As final considerations I identified that leisure has been part of the training process of PST professionals since 2003, although it has only become officially part of the program since 2009. Regarding the understanding of leisure present in the documents, I observed they do not have the same approach, which creates a mismatch in the work with leisure. Among the elected knowledges I found perspectives that relate it to a market view that have as emphasis the consumption of cultural practices, as well as other understanding anchored on leisure as social right and that opposes the logic of leisure as merchandise. Finally, the methodologies found to work leisure since 2009 were the Projeto Recreio nas Férias, the educational technology known as Animação Cultural and the work with the idea of leisure. Thus, the manners of treating leisure in the capacitation process of the program can enable processes of reflection by the professionals about the relations in which leisure is involved.